Structuring colloidal gels via micro-bubble oscillations. Issue 15 (29th March 2023) - Torre, K. W.; de Graaf, J.
Abstract : Using Brownian dynamics simulations, we show that an oscillating microbubble can locally crystallize an attractive colloidal gel above a threshold frequency. We relate this to the moving interface's ability to extract colloids from the gel network. Abstract : Locally (re)structuring colloidal gels – micron-sized particles forming a connected network with arrested dynamics – can enable precise tuning of the micromechanical and -rheological properties of the system. A recent experimental study [B. Saint-Michel, G. Petekidis, and V. Garbin, Soft Matter, 2022, 18, 2092] showed that local ordering can be rapidly induced by acoustically modulating an embedded microbubble. Here, we perform Brownian dynamics simulations to understand the mechanical effect of an oscillating microbubble on the next-to-bubble structure of the embedding colloidal gel. Our simulations reveal hexagonal-close-packed structures over a range that is comparable to the amplitude of the oscillations. However, we were unable to reproduce the unexpectedly long-ranged modification of the gel structure – dozens of amplitudes – observed in experiment. This suggests including long-ranged effects, such as fluid flow, should be considered in future computational work.